Cool Jupiters greatly outnumber their toasty siblings: occurrence rates from the Anglo-Australian Planet Search. Issue 1 (9th December 2019) - Wittenmyer, Robert A; Wang, Songhu; Horner, Jonathan; Butler, R P; Tinney, C G; Carter, B D; Wright, D J; Jones, H R A; Bailey, J; O'Toole, S J; Johns, Daniel
ABSTRACT: Our understanding of planetary systems different to our own has grown dramatically in the past 30 yr. However, our efforts to ascertain the degree to which the Solar system is abnormal or unique have been hindered by the observational biases inherent to the methods that have yielded the greatest exoplanet hauls. On the basis of such surveys, one might consider our planetary system highly unusual – but the reality is that we are only now beginning to uncover the true picture. In this work, we use the full 18-yr archive of data from the Anglo-Australian Planet Search to examine the abundance of 'cool Jupiters' – analogues to the Solar system's giant planets, Jupiter and Saturn. We find that such planets are intrinsically far more common through the cosmos than their siblings, the hot Jupiters. We find that the occurrence rate of such 'cool Jupiters' is $6.73^{+2.09}_{-1.13}$  per cent, almost an order of magnitude higher than the occurrence of hot Jupiters (at $0.84^{+0.70}_{-0.20}$  per cent). We also find that the occurrence rate of giant planets is essentially constant beyond orbital distances of ∼1 au. Our results reinforce the importance of legacy radial velocity surveys for the understanding of the Solar system's place in the cosmos.